An Analysis of Insurance Liability and The Legal Liability of Shipping Companies For Oil Spills at Sea (The Montara Case Study) - Tiara Putri Ayu Setyaningrum; Virza Aulia Arifin; Zahrian Kusuma Nur Arsy; Jihan Putri Faradyva; Khisya Valisha Arkemevira Rachmadi (Anthroposia: Journal of Social and Human Development, 2026)
The Montara oil spill case that occurred in the Timor Sea in 2009 had environmental, economic and social impacts on Indonesian waters, especially in East Nusa Tenggara. This case raises various issues regarding the legal responsibility of carriers and the role of insurance mechanisms in providing protection against losses due to transboundary marine pollution. This research aims to analyze the legal liability of carriers and its relationship with insurance mechanisms in resolving losses due to oil spills at sea. The research method used is normative juridical with a statutory and case approach. The research results show that the Montara oil spill includes marine pollution due to high-risk activities which give rise to absolute responsibility (strict responsibility) for business actors. The pollution pays principle strengthens the perpetrator's obligation to bear losses through a compensation mechanism that is ideally supported by an environmental insurance scheme or third party liability insurance. The insurance claims mechanism process in the case of countries experiences differences in laws and regulations so that this has an impact on the claims process.